Serwis Informacyjny / Biuro Informacyjne MKZ Wrocław . no. 23, 1981 - Biuro Informacyjne MKZ Wrocław, [ed. Zenon Pałka, Marcjanna Śliwińska, Ksenia Wierzbicka], Biuro Informacyjne MKS Wrocław (BI MKZ, 1981)
Print run: 5000-10000 copies